Effects of parallel code system on International students in Iceland - Fatima Norma Oaes 1996- (2021)
Iceland is a monolingual state facing the challenge of maintaining a strong national identity while faced with the potential threat of English quickly becoming a lingua franca. Higher education institutions must maintain and protect the Icelandic language and culture, simultaneously building an internationally recognized image, hence the many inconsistencies between the language policy and the goals these institutions have set in place. This review seeks to identify and discuss inconsistencies found in the language and strategic policies of the three main universities in Iceland that are aimed at international collaboration and how the rise in English as lingua franca in Iceland has left foreign and international students struggling to find their place at university. Equally important, the review discusses the inequities international students experience at the University of Akureyri, University of Iceland and Reykjavík University respectively. The aforementioned universities operate on a parallel code system in which the receptive and productive languages are not the same, meaning that textbooks and reading material is in English whereas teaching is conducted in Icelandic. However, these institutions fail to recognize the cognitive and emotional constraints the parallel code system has on both international and native students. The universities promote the idea of internationalization without the necessary provision of resources to accommodate a non-native audience i.e. international students. Furthermore, the review points out how the word “international” may be miscommunicated. The research reviewed in this paper presents that only a few courses are taught in English at undergraduate level and 90% of the textbooks are in English. Finally, there is a need to recognize that all students deserve equal opportunities and access to a variety of study programs in English, this will result in students having the academic freedom to make choices that better align with their personal goals and accommodate their ...